Analise complementar de parâmetros fisicos referentes ao número de passadas do trator em plantio direto - Dantas, Halerrandro de Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
Unplanned traffic is an alternative to mechanical growth, hampering the root development of the plant, absorbing nutrients and water, committing to produce and generate greater financial costs for the cultivation of the land. The present work is a complementary analysis of the recall program on the number of tractor passes and no-till. Quantifying an interaction of soil penetration, induced by the traffic of a tractor, the action in two no-tillage systems: (a) soil with maize crop and (b) soil with bean crop. A field experiment was conducted in a completely randomized design in a Red Latosol at the Experimental Nucleus of Agricultural Engineering of the University of the West of Paraná - UNIOESTE, to determine the compacting of the soil layers due to different passes of a FORD 7630 tractor 4x2 TDA with weight of 61 kN. The number of passages was 1, 5 and 10. Soil density, water content and soil penetration resistance were measured for compaction at 8 equal intervals of 5 cm below the soil surface before passage , after a passage and after a harvest of the installed culture. Corn and bean crops were used in the experiment. The impact of the greater number of passes in the compaction was more effective in the depth of the ground up to 20 cm. At depth of 20-40 cm, soil resistance to penetration also increased with increasing number of passes, but to a lesser extent. The values of soil resistance to penetration, after a harvest, only increased the experiment with the bean to depths of 10 to 25 cm when compared to 10 passes of the tractor, revealing an absence or effect of small elements in soil compaction during the crop cycle after as passes.
Monografia
Keywords: Compactação; Tráfego; Resistencia; Umidade; Solo; Compaction; Resistance; Traffic; Moisture; Ground; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA